Pemberdayaan Masyarakat dalam Penyusunan Peta Persebaran Produk UMKM Desa Buncitan - Shofwan, Moch; Sagung Alit Widyastuty, Anak Agung; Rohmadiani, Linda Dwi; Suning, Suning; Rukmana, Siti Nuurlaily; Tribhuwaneswari, Annisa Budhiyani (Universitas Pahlawan Tuanku Tambusai, 2024)
Buncitan Village is one of the UMKM villages in Sidoarjo which is located near the east coast of Sidoarjo. Based on the results of the 2023 survey, Buncitan Village has the potential for small-scale industries, especially household industries such as the food and beverage industry, weaving, and so on. The types of MSMEs in this village are quite diverse, so a spatial location should be made for the location of the MSMEs for each type in the form of a map of the distribution of MSMEs. The purpose of this PKM is community empowerment in making maps of the distribution of MSMEs in order to increase sales of Buncitan Village, Sedati District, Sidoarjo Regency. The solution offered is the dissemination of understanding and empowerment of making maps of the distribution of MSMEs in Buncitan Village. Based on the results of this PKM activity, it can be seen the types of businesses and MSMEs in Buncitan Village along with their distribution of spatial patterns.